Pricing the Transfer of Intellectual Property: A Plea for Regulated and Internationally Coordinated Profit Splitting - Wolfram F. Richter; Markus Breuer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Taxing intellectual property effectively is a challenging task. With its BEPS initiative the OECD (2013) aims at taxing intangibles in accordance with value creation although difficulties in determining the jurisdiction in which value creation occurs are acknowledged. The European Commission promotes the introduction of a Common Consolidated Corporate Tax Base (CCCTB) to neutralize profit shifting. The drawback of this proposal is that incentives are set to relocate R&D activities to low-tax countries. This is the background against which the present paper pleads for a regulated and internationally coordinated split of the profits earned with licensed know-how.
Keywords: H25; O34; M48; 330